Pest categorisation of Pantoea stewartii subsp. stewartii - Jeger, Michael (John Wiley and Sons Inc., 2018)

(untitled) (EFSA J)
Following a request from the European Commission, the EFSA Plant Health Panel performed a pest categorisation of Pantoea stewartii subsp. stewartii (hereafter P. s. subsp. stewartii). P. s. subsp. stewartii is a Gram‐negative bacterium that causes Stewart's vascular wilt and leaf blight of sweet corn and maize, a disease responsible for serious crop losses throughout the world. The bacterium is endemic to the USA and is now present in Africa, North, Central and South America, Asia and Ukraine. In the EU, it is reported from Italy with a restricted distribution and under eradication. The bacterium is regulated according to Council Directive 2000/29/EC (Annex IIAI) as a harmful organism whose introduction and spread in the EU is banned on seeds of Zea mays. Other reported potential host plants include various species of the family Poaceae, including weeds, rice (Oryza sativa), oat (Avena sativa) and common wheat (Triticum aestivum), as well as jackfruit (Artocarpus heterophyllus), the ornamental Dracaena sanderiana and the palm Bactris gasipaes, but there is uncertainty about whether these are hosts of P. s. subsp. stewartii or of the other subspecies. The pest could enter the EU via host plants for planting (including seed) and via insect vectors from neighbouring countries. Host plants are widely distributed and climatic conditions are conducive in the EU. P. s. subsp. stewartii could spread by movement of host plants for planting (including seeds) and insect vectors. Impacts could occur on maize and rice. Methods to certify pest freedom of maize seeds are available. The main knowledge gaps concern the availability of vectors in the EU, the level of susceptibility of the maize cultivars grown in the EU, the virulence of strains in recent outbreaks, and the host range of the bacterium. The criteria assessed by the Panel for consideration as a potential quarantine pest are met.